TB HIV Control Program Problem Analysis in Gresik District Health Office - Sholikah Sholikah; Atik Choirul Hidajah; Bambang Wuryono Kartika (Health Notions, 2018)
Introduction. Health problems in Gresik district were diverse. Ideally, all existing problems must be solved, but because of limited resources, not all problems can be resolved at once. The purpose of problem analysis was to determine the problem considered as the most priority and can be used as a basis for effective and efficient program planning and evaluation. Methods used in determining priority problem were Urgency, Seriuosness, and Growth (USG) and root cause analysis by fishbone diagram. Whereas to determine the root priority of the problem, the Rienke method was used. Health problem analysis activities at Gresik District Health Office was executed on January 3 to February 3, 2017. The data used for this analysis came from secondary data. Results shows that the low number of TB-HIV patients receiving ARVs was a priority issues in Gresik District Health Office. Based on the fishbone diagram, the patient's lack of understanding about the importance of ARVs causes low number of TB-HIV patients receiving ARVs. Conclusion. Utilizing peer support group as a medium for counseling and training was needed to increase understanding about ARVsimportance to TB-HIV patients. Keywords: TB-HIV, Urgency, Seriousness, Growth, TB-HIV